Colonized Black Women's Bodies Resisting Oppression in Morrison's Beloved and Walker's Possessing the Secret of Joy - ÖZTÜRK, MAKBULE (İstanbul Kültür Üniversitesi, 2023)
This study investigates the marginalization and violation of black female bodies within the oppressive power mechanisms of the colonial and patriarchal ideologies in Toni Morrison's Beloved (1987) and Alice Walker's Possessing the Secret of Joy (1992). Resistance of the oppressed bodies of female characters is scrutinized through a comparative analysis. Postcolonial and black feminist/womanist points of view along with a feminist understanding of the so-called subordination of black female bodies are applied in a deconstructive method. The colonial and patriarchal ideologies are put under scrutiny to show that these two ideologies resemble each other in terms of their hegemonic structures highlighting the dichotomized thinking inherent in the western understanding which leads to the so-called subordination of black women. Logocentrism of the colonial system and phallocentrism of the black patriarchal perspective locating black women in the "inferior other" position of the binarized thinking is demystified. For this end, Michel Foucault's idea of power and knowledge; remarks of bell hooks, Angela Davis and Audre Lorde on the state of black female bodies in the sexist-racist systems along with Morrison's concept of Africanism are referred to deconstruct the binarized thinking. Additionally, the womanist discourse of Toni Morrison and Alice Walker; and feminist perspectives of Hélène Cixous and Luce Irigaray's theories of repression of the female body are visited to undo the discourse of the power. This study problematizes the colonizing mentality prevailing in American society through the analysis of Toni Morrison's Beloved and shows that the same colonizing manner is mirrored in the fictional Olinkan tribe in Alice Walker's Possessing the Secret of Joy. The female characters in both novels carry the traces of the brutal treatment on their bodies but strike the reader as defying characters to the manipulations of the oppressive systems through resorting to violence as a means of resistance, thereby moving from the state of passivity to activity by taking control of their lives.
Morrison'ın Sevilen ve Walker'ın Sevincin Sırrına Sahip Olmak'ta Baskıya Direnen Sömürgeleştirilmiş Siyah Kadın Bedenleri
▪ Yüksek lisans tezi.
Keywords: Black Body; Colonialism; Patriarchy; Resistance; Oppression; Power; Violence; Toni Morrison; Beloved; Alice Walker; Possessing the Secret of Joy